Hardware-friendly neural network design and optimization for low power IOT applications - Wang, Yingfeng (Nanyang Technological University, 2022)
As speech becomes a popular way for human to interact with electronic devices in recent years, it leads to interests to apply machine learning in speech related applications, such as sound classification, speech recognition and so on.